Volcanic hazards, risks and disasters - Papale, Paolo (Amsterdam Elsevier, 2015)
Volcanic Hazards, Risks, and Disasters provides you with the latest scientific developments in volcano and volcanic research, including causality, impacts, preparedness, risk analysis, planning, response, recovery, and the economics of loss and remediation. It takes a geoscientific approach to the topic while integrating the social and economic issues related to volcanoes and volcanic hazards and disasters. Throughout the book case studies are presented of historically relevant volcanic and seismic hazards and disasters as well as recent catastrophes, such as Chile’s Puyehue volcano eruption in June 2011.--Provided by publisher.
Machine generated contents note: Introduction; Volcanoes and plate tectonics; Volcanic form and structure; Types and characteristics of central eruptions and extended lateral eruptions; Physics of volcanism; Historical eruptions; Volcano magnitudes and impacts; Volcanic products: volatiles; Volcanic products; pyroclastics; Volcanic products: Lava flows and shallow intrusions; Volcanic products: Craters, calderas, and super-eruptions; Volcanoes and water/Lahars; Paleoeruptions and dating; Volcanic stratigraphy and tephrochronology; Archaeological evidence of volcanism; Volcanoes and mythology; Volcanic hazard and prediction (periodicities); Field investigation techniques; Community coping strategies.
Electronic reproduction.
Keywords: Volcanic hazard analysis; Electronic books